2020
DOI: 10.1002/ptr.6970
|View full text |Cite
|
Sign up to set email alerts
|

Natural compound catechol induces DNA damage, apoptosis, and G1 cell cycle arrest in breast cancer cells

Abstract: Targeting cell cycle and inducing DNA damage by activating cell death pathways are considered as effective therapeutic strategy for combating breast cancer progression. Many of the naturally known small molecules target these signaling pathways and are effective against resistant and/or aggressive types of breast cancers. Here, we investigated the effect of catechol, a naturally occurring plant compound, for its specificity and chemotherapeutic efficacies in breast cancer (MCF‐7 and MDA‐MB‐231) cells. Catechol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Catechol has oxidative-reductive activity and can induce further membrane damage. Additionally, after membrane damage, CA can more easily enter cells and cause genetic toxicity such as DNA and protein damage ( Vazhappilly et al, 2021 ). Therefore, these may be the reasons why ERG2 and ERG6 knockout strains are extremely sensitive to CA stress.…”
Section: Discussionmentioning
confidence: 99%
“…Catechol has oxidative-reductive activity and can induce further membrane damage. Additionally, after membrane damage, CA can more easily enter cells and cause genetic toxicity such as DNA and protein damage ( Vazhappilly et al, 2021 ). Therefore, these may be the reasons why ERG2 and ERG6 knockout strains are extremely sensitive to CA stress.…”
Section: Discussionmentioning
confidence: 99%
“…Guo Y et al ( Guo et al, 2021a ) concluded that ATR-CHK1 signaling would be a therapeutic target for liver cancer. As reported, the role of ATR-CHK1 has been considered as a necessary regulator of the DDR, which especially involved in sensing DNA replication stress ( Smith et al, 2020 ; Khazaaleh et al, 2021 ; Vazhappilly et al, 2021 ). Further, this signal could activate oncogene and regulate G1 checkpoint ( Khazaaleh et al, 2021 ).…”
Section: Resistance Mechanismmentioning
confidence: 96%
“…In 2021, a study by Vazhappilly et al indicated that catechol could inhibit proliferation and result in apoptosis in MCF-7 cells by activating p53, inhibiting of regulatory proteins such as DNMT1, P-BRCA1, Mcl-1, and PDCD6, and increasing the Bax/Bcl-2 ratio. Ultimately, caspase-mediated cell death is triggered (Vazhappilly et al, 2021). In their study, Sp et al (2021) showed that 6-zingerol might induce apoptosis in MDA-MB-231 and MCF-7 BC cell lines by activating p53, regulating the Bax/ Bcl-2 ratio, and increasing the release of CytoC.…”
Section: Mitochondrial Pathway-mediated Apoptosismentioning
confidence: 98%